Bitter frankincense water modulates hepatic enzyme activity in female patients with irritable bowel syndrome: Bitter frankincense water reduces liver enzymes in IBS - Khamaal Hussein Abod Al-Khafaji,,; Zahraa Mohammed Fakheir,,; Shaimaa Mohammed Ali Jasim, (Cellular and Molecular Biology, 2025)
This study aimed to determine and know the effect of bitter frankincense water on the levels of the functional liver enzymes in female patients with irritable bowel syndrome. This study was conducted in the consulting laboratories for pathological analyses in Iraq for the period from January to February 2025. The study was applied to 25 female patients, whose ages ranged from 20 to 65 years and healthy group consisted of 25 females, aged between 20 – 65. Bitter frankincense water, was bought from reputable local markets, enough to feed 25 female patients for two months. The amount was 3 ml/kg, and each female patient was given the dose according to his weight. This is done by dividing the dose in half, for the morning and for the evening. Before administering bitter frankincense water to female patients with irritable bowel syndrome, a five milliliter blood sample was obtained, and the liver enzymes were evaluated for the samples, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT). Subsequently, samples were collected from the same group of female patients with irritable bowel syndrome to compare the effects of bitter frankincense water before and after giving. The results of the study showed a significant decrease (P<0.05) in the levels of liver function enzymes, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT) in patients with irritable bowel syndrome in women after these patients took doses of FWB. The study's notable reduction in liver enzyme levels suggests that FWB may be a useful natural hepatoprotective treatment for people with IBS. These results encourage more investigation into FWB as a supplemental treatment for enhancing gut-liver axis balance and liver function in IBS patients.